(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This research paper delves into the pivotal role of green chemistry in advancing sustainable development, a crucial aspect in the face of escalating environmental challenges. Green chemistry, defined as the design of chemical products and processes that minimize the use and generation of hazardous substances, significantly contributes to reducing the environmental impact associated with traditional chemical practices. Prioritizing renewable resources and energy-efficient methods, green chemistry enhances resource efficiency, leading to lower waste generation and reduced consumption of non-renewable materials. This field fosters innovative practices that not only mitigate ecological damage but also stimulate economic growth. For instance, the development of biodegradable materials and environmentally benign solvents exemplifies how green chemistry can lead to safer consumer products while also creating market opportunities in the burgeoning field of sustainable materials. Aligned with global sustainability goals, green chemistry supports initiatives such as the United Nations Sustainable Development Goals (SDGs), particularly those focused on responsible consumption and production. Iintegrating principles of green chemistry into industrial processes, research, and education, this approach offers a transformative pathway towards a more sustainable and resilient future, emphasizing the importance of chemistry as a driver of environmental stewardship and economic innovation.